2017
DOI: 10.3168/jds.2016-11534
|View full text |Cite
|
Sign up to set email alerts
|

Production of reuterin in a fermented milk product by Lactobacillus reuteri: Inhibition of pathogens, spoilage microorganisms, and lactic acid bacteria

Abstract: We assessed the antimicrobial activity of reuterin produced in vitro in glycerol aqueous solutions in situ by Lactobacillus reuteri ATCC 53608 as part of a fermented milk product against starter (Lactobacillus delbrueckii ssp. bulgaricus and Streptococcus thermophilus), spoilage (Penicillium expansum), pathogenic (Staphylococcus aureus Salmonella enterica ssp. enterica, and Listeria monocytogenes), and pathogen surrogate (Escherichia coli DH5α) microorganisms. We also assayed the influence of cold storage (28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 41 publications
4
54
1
2
Order By: Relevance
“…Langa and coauthors [3] obtained results of reuterin concentration between 0.21 and 0.75 mM for the different strains used in yogurt produced with 100 mM of glycerol, under similar conditions to the present work. Ortiz-Rivera and coauthors [4] presented higher concentrations of reuterin in situ in fermented milk compared to our study. However, the same authors reported that S. aureus presented resistance up to 1.5 mM of reuterin while in the present study the concentration of 0.40 ± 0.05 mM was sufficient to inhibit both S. aureus strains tested.…”
Section: Reuterin Inhibition and Quantitation Assaycontrasting
confidence: 55%
“…Langa and coauthors [3] obtained results of reuterin concentration between 0.21 and 0.75 mM for the different strains used in yogurt produced with 100 mM of glycerol, under similar conditions to the present work. Ortiz-Rivera and coauthors [4] presented higher concentrations of reuterin in situ in fermented milk compared to our study. However, the same authors reported that S. aureus presented resistance up to 1.5 mM of reuterin while in the present study the concentration of 0.40 ± 0.05 mM was sufficient to inhibit both S. aureus strains tested.…”
Section: Reuterin Inhibition and Quantitation Assaycontrasting
confidence: 55%
“…Shahani et al (1976) noted strong inhibitory effects of an inhibitory compound from L. acidophilus against 8 pathogens, and Shahani et al (1972) patented the antibiotic acidophilin that is produced by various strains of L. acidophilus, especially L. acidophilus DDS 1. Recently, Ortiz-Rivera et al (2017) showed that reuterin produced by L. reuteri ATCC 53608 can inactivate pathogenic (S. aureus, Salmonella enterica ssp. enterica, and L. monocytogenes), pathogen indicator (E. coli DH5α), and spoilage (Penicillium expansum) microorganisms.…”
Section: Health Benefits Provided By Yogurt and Other Cultured Dairy mentioning
confidence: 99%
“…The ability to produce this bacteriocin was verified using the colorimetric test described by Cadieux et al (2008) on a 24-h culture of the strain grown in MRS medium supplemented with glycerol (250 mM final concentration). The principle behind the test is that of transforming glycerol into 3-hydroxypropionaldehyde (reuterin) and to quantify it using a spectrophotometric method at 560 nm (Doleyres et al, 2005;Ortiz-Rivera et al, 2017).…”
Section: Reuterin Secretionmentioning
confidence: 99%